2020
DOI: 10.3390/ma13163480
|View full text |Cite
|
Sign up to set email alerts
|

Correlation among the Power Dissipation Efficiency, Flow Stress Course, and Activation Energy Evolution in Cr-Mo Low-Alloyed Steel

Abstract: In the presented research, conventional hot processing maps superimposed over the flow stress maps or activation energy maps are utilized to study a correlation among the efficiency of power dissipation, flow stress, and activation energy evolution in the case of Cr-Mo low-alloyed steel. All maps have been assembled on the basis of two flow curve datasets. The experimental one is the result of series of uniaxial hot compression tests. The predicted one has been calculated on the basis of the subsequent approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…Similar flow-stress-like behavior has been observed e.g. in [7]. Nevertheless, the trends observed under lower temperatures are not in accordance with those observed under higher temperatures -Q-ε curves seem to be mirror-invertedthey show a global minimum.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…Similar flow-stress-like behavior has been observed e.g. in [7]. Nevertheless, the trends observed under lower temperatures are not in accordance with those observed under higher temperatures -Q-ε curves seem to be mirror-invertedthey show a global minimum.…”
Section: Resultssupporting
confidence: 64%
“…In these equations, σ (MPa), ε (-), ε̇ (s −1 ) and T (K) represent a flow stress, true strain, strain rate and temperature, respectively. R (8.314 J⋅K −1 ⋅mol −1 ) is the universal gas constant, α(ε,T) (MPa −1 ) and α(ε) (MPa −1 ) are a strain-temperature dependent and only-strain dependent stress multiplier, respectively [7].…”
Section: Extraction Of Experimental Activation Energy Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, one of the hot deformation optimization approaches for Ti-1023 alloy was the use of processing maps based on dynamic materials modeling (DMM) [17,18]. Superimposing hot processing maps over flow stress maps as well as overactivation of energy values to evaluate the hot workability of the investigated materials is quite often applied [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the Z parameter is used to characterize the relationship between strain rate, deformation temperature and flow stress. Many studies have shown that the Z parameter can reflect the type of softening mechanism [33,34]. The lower lnZ value can promote the process of nucleation and growth of dynamic recrystallization (DRX) grains.…”
Section: Processing Map and Activation Energy Mapmentioning
confidence: 99%